Physiological and transcriptomic analyses of leaves from Gardenia jasminoides Ellis under waterlogging stress - Feng,Z. (2024)
Abstract Gardenia jasminoides Ellis is a Chinese herbal medicine with medicinal and economic value, but its mechanism of response to waterlogging stress remains unclear. In this study, the “double pots method” was used to simulate the waterlogging stress of Gardenia jasminoides Ellis to explore its physiological and transcriptomic response mechanism. We found no significant damage to Gardenia jasminoides Ellis membrane lipid during stress. POD played a vital antioxidant role, KEGG enrichment showed that secondary metabolites such as flavonoids might also play an antioxidant role, and PRO played a significant osmotic adjustment. Endogenous hormones regulate the Gardenia jasminoides Ellis's growth and development and play a role in signal transduction. Among them, light waterlogging stress is delayed. At the same time, there were 19631, 23693, and 15045 differentially expressed genes on the 5th, 10d, and 15d of Gardenia jasminoides Ellis under waterlogging stress. These genes were closely associated with the proteasome, endopeptidase, ribosome, MAPK signal transduction, and endogenous hormone signal transduction, plant-pathogen interaction and phenylpropanoid biosynthesis and other physiological and metabolic pathways, which regulate the turnover and transportation of protein, the reinforcement and adhesion of cell walls, the induction of stomatal closure, allergic reactions, defense reactions, leaf movements and others. It also can absorb ultraviolet rays to reduce the generation of oxygen free radicals, change the way of energy utilization and adjust the osmotic pressure of plant cells.